2013
DOI: 10.1186/1743-7075-10-46
|View full text |Cite
|
Sign up to set email alerts
|

Milk protein for improved metabolic health: a review of the evidence

Abstract: Epidemiological evidence shows that consumption of dairy products is associated with decreased prevalence of metabolic related disorders, whilst evidence from experimental studies points towards dairy protein as a dietary component which may aid prevention of type 2 diabetes (T2DM). Poor metabolic health is a common characteristic of overweight, obesity and aging, and is the forerunner of T2DM and cardiovascular disease (CVD), and an ever increasing global health issue. Progressive loss of metabolic control is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
133
1
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(143 citation statements)
references
References 119 publications
(178 reference statements)
1
133
1
8
Order By: Relevance
“…Whey proteins help to control the blood glucose levels and also provides additional beneficial for weight management which is a concern for type-2 diabetics (Shankar and Bansal, 2013). Ingestion of whey proteins lead to more rapid secretion of insulin than micellar casein (McGregor and Poppitt, 2013).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Whey proteins help to control the blood glucose levels and also provides additional beneficial for weight management which is a concern for type-2 diabetics (Shankar and Bansal, 2013). Ingestion of whey proteins lead to more rapid secretion of insulin than micellar casein (McGregor and Poppitt, 2013).…”
Section: Human Immunodeficiency Virus (Hiv)mentioning
confidence: 99%
“…This effect is thought to be related to the sulfhydryl component, particularly cysteine and its link with glutamic acid in the production of glutathione. In a study by Rosaneli et al (2002), rats fed a whey protein concentrate showed a 41% reduction in ulcerative lesions caused by ethanol ingestion while, a 73% reduction rate was observed following repeat doses of whey (Marshall, 2004;McGregor and Poppitt, 2013).…”
Section: Cardiovascular Disease Preventionmentioning
confidence: 99%
“…Selective elution, also known as ion exchange chromatography, is the process most often used to produce whey protein isolates [14]. Additional hydrolysis with enzymes or acids provides a way to breakdown the structure of protein containing in whey [22]. As the acids hydrolysis process would also lower the quality and biological value of protein, the addition of proteolytic enzymes, followed by purification procedures is greatly preferred [32].…”
Section: Milk Composition: Protein Sub-fractions Manufacturing and Mamentioning
confidence: 99%
“…All of these components have been associated with the potential to improve general health outcomes and disease prevention reduce immunosuppression attenuate muscular inflammatory related damage optimize recovery process and resistance training outcomes in athletes and enhance metabolic health in general population [19][20][21][22][28][29][30].…”
Section: Milk Composition: Protein Sub-fractions Manufacturing and Mamentioning
confidence: 99%
See 1 more Smart Citation